Are All Types of Cooperation Equal? Impact of Academic Controversy Versus Concurrence-Seeking on Health Education - Mitchell, James M.; Johnson, David W.; Johnson, Roger T. (Social Psychology of Education, 2002)
Cooperative learning is commonly used to promote prosocial outcomes. It is often assumed that all types of cooperative learning are equal. One way in which cooperative learning procedures differ is in the role of conflict. This study compares the relative impact of two types of cooperative learning (concurrence-seeking which emphasizes harmony among students and academic controversy which emphasizes intellectual conflict among students) on outcomes of a health education program focusing on tobacco use, alcohol use, and AIDS. Participants were 37 students from grades 9–12 in a career-education track in a suburban mid-western high school. The students were classified as being low performing academically and at risk for destructive health habits. Students in the controversy condition, compared with those in the concurrence-seeking condition, significantly improved in knowledge about AIDS, developed healthier attitudes related towards safe sex and cigarettes, developed higher academic self-esteem, generated greater social influence, and improved in constructive conflict skills.